2017
DOI: 10.1002/smll.201700709
|View full text |Cite
|
Sign up to set email alerts
|

A Graphene Quantum Dots–Hypochlorite Hybrid System for the Quantitative Fluorescent Determination of Total Antioxidant Capacity

Abstract: Antioxidants play a major part in the prevention and impairment of oxidative stress-induced damages and diseases. Evaluating the antioxidants activity/capacity in food and biological fluid is proved to be useful for the diagnosis and treatment of these oxidative stress-induced diseases. Herein, a graphene quantum dots (GQDs)-hypochlorite system to detect the antioxidants including nonenzymatic and enzymatic antioxidants in the biological fluid is proposed. The detection principle is based on the fact that anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…[6,29] The XPS spectrum of P2p exhibited two apparent peaks centred at 133.3 and 133.7 eV,w hich were relatedt ot he PÀOa nd P=Ob onds (Figure 3d). Consistent with FTIR data, the asCQDs possessed ah igherc ontent of CÀNÀCa ccompanied with ad eclined ratio of CÀOH and NÀ(C) 3 (Table S2,S upporting Information) . The results clearly demonstrated that more carboxyl and amide moieties were exhausted and repalced by amide bonds (ÀCONHR and ÀCNHR).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…[6,29] The XPS spectrum of P2p exhibited two apparent peaks centred at 133.3 and 133.7 eV,w hich were relatedt ot he PÀOa nd P=Ob onds (Figure 3d). Consistent with FTIR data, the asCQDs possessed ah igherc ontent of CÀNÀCa ccompanied with ad eclined ratio of CÀOH and NÀ(C) 3 (Table S2,S upporting Information) . The results clearly demonstrated that more carboxyl and amide moieties were exhausted and repalced by amide bonds (ÀCONHR and ÀCNHR).…”
Section: Resultssupporting
confidence: 72%
“…[1,2] These properties make CQDs superior to organic dyes and semiconductor quantum dots with heavy metal cores in biological systems, inspiring the dominatinga pplicationsi nb iosensor and bioimaging. [3][4][5][6][7][8][9][10][11][12] The hydrothermal carbonization method is considered as an efficient one-step strategy for the fabricationo fC QDsb yu sing various carbon sources.N atural biomass and synthetic chemicals have been searched and investigated as novel carbon sourcest os ynthesize fluorescentC QDs. [6,[13][14][15][16][17][18] In general, CQDs could be acquiredb yd ehydration of carbon-rich components in biomass substrates (such as polysaccharide, protein, and their mixtures), and it hasb een provedt hat the primary structure of precursors, knowna st he atomic composition and the connected chemicalb onds, determine the properties of synthetic CQDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of GQDs has also shown that these nanomaterials may have antioxidant (Zheng et al, 2015), antimicrobial (Szunerits and Boukherroub, 2016) and cytotoxic effects (Lalwani et al, 2016); therefore, they could be used in areas other than biosensing and bioimaging. For example, the chemical composition of some GQDs in relation to their antioxidant and free radical scavenging activities has been investigated and compared (Ruiz et al, 2017, Wang et al, 2017). The inhibitory effective concentration of the best performing GQDs was lower than that of ascorbic acid and other carbon nanomaterials (Ruiz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), including free radicals such as hydroxyl (•OH), superoxide (•O 2 − ), alkoxy (RO•), and peroxide (ROO•), are byproducts of cellular redox processes. ROS can contain one or more unpaired electron and are, therefore, highly reactive [1][2][3][4]. In general, ROS play a dual role in biological systems.…”
Section: Introductionmentioning
confidence: 99%